Thalamocortical relations in the brain of the frog, Their role in the genesis of epileptic electrographic phenomena - Servít, Z; Strejcková, A (Physiologia Bohemoslovaca, 1975)
The existence of a thalamocortical reverberating circuit between the dorsal thalamic and primordial hippocampal structures could be proved in the brain of the frog (Rana temporarial) by evoking recruiting potentials. Unlike the turtle, this circuit does not take part in the genesis of electrographic phenomena in the corticogram of the frog under normal resting conditions. Spindle activity could not be observed in the EEG of curarized frogs. On the other hand, thalamic structures can influence paroxysmal susceptibility of the frog forebrain. The generation of the penicillin focus could be accelerated and paroxysmal electrographic activities elicited by iontophoretic application of penicillin into dorsal thalamic structures and/or rhythmic electric stimulation of this region. The features of thalamocortical cooperation in the frog and in the turtle have been compared.
Keywords: žáby; Evoked Potentials; Anura; Thalamus; mozková kůra; zvířata; evokované potenciály; Somatosensory Cortex; thalamus; Cerebral Cortex; somatosenzorické korové centrum; Rana temporaria; hipokampus; Hippocampus; Animals